Model Pengembangan Kriteria Desain Rusunawa Berdasarkan Kepuasan Penghuni: Studi Kasus, Rumah Susun Sederhana Sewa Kutobedah di Kota Malang - Subagijo, Edi; Suhartono, Tonny (RUANG: Jurnal Lingkungan Binaan (SPACE: Journal of the Built Environment), 2018)
The development of rented multi-storey housing unit ( rusunawa ) is a logical event in the growth of cities. Sooner or later the development of rusunawa will be increasingly implemented in urban areas in Indonesia. Despite the fact that people will be housed in rusunawa , it is important that kinship in the community should be maintained, thus supporting communal ties, social interaction and neighbourliness. Results of the following study into community identity support these general principles. The research method adopted used both quantitative and qualitative techniques to assess residents' satisfaction, behavioral patterns and forms of social interaction. The research suggests design criteria to support residents' satisfaction with their dwelling. The research also models the patterns of residents in public spaces (hallway, kitchen and lavatories) to measure social interaction. The research case study is located in Kutobedah Rusun awa as the first rusunawa constructed by the government of Malang City in 1995. Keywords: rusunawa, satisfaction, behavior pattern